9th Five Year Plan 1997-2002 Volume-IV Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
During 9th plan, we propose to purchase adequate BEST equipments for stations which are not equipped with this system of communication, HF R/T communication for southern group of Islands including Look Out Posts, VHF repeater system for Andaman District with modern and sophisticated equipments, VHF reserve sets considering requirement of VIP/VVIP movements. Since, we are getting these sets from DCPW, New Delhi on loan basis with grate difficulty as and when required. Further, we propose to strengthen our workshop with adequate manpower, infrastructure, tool kits for the care and maintenance of these costly and sophisticated sets.
Andaman and Nicobar Administration, Planning Department